Hernias cerebrais intracranianas Intracranial cerebral herniations - João Guidugli Neto (Arquivos de Neuro-Psiquiatria)
O autor estuda as diferentes manifestações macroscópicas de deslocamento intracraniano de massa encefálica em 420 encéfalos. Em 23 destes havia lesão secundária do tronco cerebral. A hérnia temporal uni ou bilateral foi a alteração mais frequente no material, sendo a anóxia terminal provavelmente um dos fatores importantes no seu estabelecimento. Foi verificado decréscimo acentuado das lesões secundárias do tronco cerebral após os 60 anos de idade. Intracranial cerebral herniations occurring in 420 brains from consecutive necropsies are studied. They were present in 65 brains; in 23 there was secondary lesions in the upper brainstem. Temporal herniations in one or both sides, was the most frequent finding. Terminal anoxia is believed to be one of the most important factors. There was decrease of the secondary lesions of the brainstem after 60 years of age.